(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Background: Although children have been mostly unaffected by the immediate health implications of COVID-19, the crisis has had a significant impact on their overall well-being. Objective: Our study was aimed to assess outcomes related to the positive impact of family physicians in the provision of primary health care to Iraqi children with COVID-19. Patients and methods: Clinical data was collected from different hospitals in Iraq between 15th July 2022 and 9th March 2023. The outcomes associated with paediatric patients, including age, sex, body mass index, symptoms, duration, comorbidities, treatment, and economic status of the parents, were summarised through clinical and demographic data characteristics. Quality of life outcomes of paediatric patients were evaluated using the Peds QL scale. Patient satisfaction ratings were derived from medical performance in relation to patients’ quality of life, which were categorized as excellent, satisfactory, or poor. Results: Clinical demographic data indicated a higher incidence of Coronavirus infection among males (57.83%) compared to females (42.17%). Although not all children display symptoms, our study found that fever (27.21%), cough (22.89%), headache (13.25%), and nasal congestion (14.46%) were the most common symptoms in pediatric patients. This study used the Peds QL scale to evaluate the quality of life of pediatric patients infected with COVID-19. This study played a constructive role in enhancing the quality of life of patients during healthcare, with specific emphasis on physical (92.78 ± 5.3) and school functioning (86.81 ± 8.52). Conclusion: Clinical results showed that health care has significantly contributed to improving the quality-of-life rates of pediatric patients infected with COVID-19. The physical aspect and school functioning were the most prominent successes in the health condition of patients after Corona.